73.2k views
2 votes
Which system is equivalent to 3x^2 - 4y^2 = 25

-6x^2 - 2y^2 = 11

Answer choices available:
A) 3x^2 - 4y^2 = 25
12x^2 + 4y^2 = 22

B) 3x^2 - 4y^2 = 25
-12x^2 + 4y^2 = 22

C) 6x^2 - 8y^2 = 25
-6x^2 - 2y^2 = 11

D) 6x^2 - 8y^2 = 50
-6x^2 - 2y^2 = 11

As always, thank you for your help!

User ObjectDB
by
6.8k points

2 Answers

3 votes

Answer:

d.

Explanation:

User Zvonimir
by
7.9k points
3 votes

For this case we have the following system of equations:


image

We can write a system of equivalent equations.

For this, it is enough to multiply one of the two equations by a scalar.

Multiplying the equation 1 by 2, we have:


image

Therefore, the new system of equations is:


image

Answer:

A system that is equivalent is:

D)
image

User Rahul Kumar Dubey
by
7.8k points